ILRI/BMZ Safe Food Fair Food: Building capacity to improve the safety of animal-source foods and ensure continued market access for poor farmers in sub-Saharan Africa - Makita, K.; Grace, Delia; Baumann, M.P.O.; Bräunig, J.; Randolph, Thomas F.; Baker, Derek; Unger, Fred (International Livestock Research Institute, 2010)
In developing countries, food-borne diseases are one of the most important public health problems and animal-source foods cause a large proportion of such diseases. In sub-Saharan Africa where many people live in poverty, the level of food hygiene is very low. This is not only because living environment is generally unhygienic but also most of marketed foods are distributed through informal value chains which are not regulated by the governments. The Safe Food, Fair Food (SFFF) project, funded by BMZ, is building capacity in risk analysis, which has greatly improved food safety in developed countries, to resource-poor sub Saharan Africa. Adaption of risk analysis involves participatory methods to assess risks of animal source food borne diseases and explore feasible measures for improvement of food safety driven by consumers and market participants themselves. The SFFF project has several steps. Firstly a food safety situational analysis is carried out by stakeholders of food safety in the participating countries and problems are identified. Tailored training is given with the collaboration of German institutes (Federal Institute for Risk Analysis: BfR and Free University of Berlin: FUB). The important problems identified are investigated by graduate students using participatory risk analysis. This involves developing solutions for improving food safety while ensuring continued access to markets for smallholder producers and participants in informal marketing. At the same time, capacity to carry out such studies is developed. The results gained from risk assessments are shared among food safety stakeholders in the National Workshops to enhance the use of such results for decision making and to make participatory risk analysis familiar to them. The 8 participating countries are Côte d'Ivoire, Ethiopia, Ghana, Kenya, Mali, Mozambique, Republic of South Africa and Tanzania, and in total 18 students are involved in the research project. A wide variety of studies is being carried out: human and animal brucellosis, E. coli O157 and Salmonella in beef, Staphylococcus aureus in milk, polycyclic aromatic hydrocarbons in smoked fish, Salmonella in chicken, game meat from National Parks, dried beef and slaughtering and consumption of meat in tribal rituals. Initial findings from these are presented.